2019
DOI: 10.15517/ijds.v0i0.36682
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrants for Aesthetic Treatment of White Spots Lesions by Fluorosis: Case Report

Abstract: Dental fluorosis is an abnormality in the development of enamel due to the excessive intake of fluoride during formation of dental tissues, mainly characterized by hypomineralization and increased porosity of the enamel structure. Oftenly the spots caused by dental fluorosis can compromise the aesthetics of the patient and affect their self-esteem. In recent years a new generation of dental materials has been developed, known as resin infiltrants, which are basically low viscosity resins that infiltrate and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…In recent years, a new, more conservative approach has been developed to stop and control initial carious lesions, using the technique with infiltrative resins, which are characterized by their low viscosity, allowing the intercrystalline spaces in the demineralized enamel to be filled, occluding the microporosities that they can act as a diffusion route for acids and dissolved materials, thus achieving the formation of a barrier within the lesion, 14 recent scientific evidence has shown that they can be used to treat dental fluorosis. [15][16][17] The low-viscosity photopolymerizable resin allows rapid penetration into the porous enamel capable of inhibiting demineralization, masking the lesions and obliterating the microporosities within the lesion. 18 When performing the infiltrating resin technique, (Figure 3) the tooth structure is preserved, it mechanically stabilizes the structure of the demineralized enamel, it occludes the micropores in the body of the lesion, there is an absence of post-treatment sensitivity and pulp inflammation, it reduces the probability of gingivitis and periodontal disease, it stops the progression of lesions and reduces the recurrence of cavities without the need to make a cavity, it does not require anesthetics, it provides excellent aesthetic results in a single visit and it is possible to obtain good acceptance by patients.…”
Section: Treatmentmentioning
confidence: 99%

Dental fluorosis: a review

Rosas López Portillo,
Rosas Alcaraz,
Gámez Valenzuela
et al. 2024
Int J Res Med Sci
“…In recent years, a new, more conservative approach has been developed to stop and control initial carious lesions, using the technique with infiltrative resins, which are characterized by their low viscosity, allowing the intercrystalline spaces in the demineralized enamel to be filled, occluding the microporosities that they can act as a diffusion route for acids and dissolved materials, thus achieving the formation of a barrier within the lesion, 14 recent scientific evidence has shown that they can be used to treat dental fluorosis. [15][16][17] The low-viscosity photopolymerizable resin allows rapid penetration into the porous enamel capable of inhibiting demineralization, masking the lesions and obliterating the microporosities within the lesion. 18 When performing the infiltrating resin technique, (Figure 3) the tooth structure is preserved, it mechanically stabilizes the structure of the demineralized enamel, it occludes the micropores in the body of the lesion, there is an absence of post-treatment sensitivity and pulp inflammation, it reduces the probability of gingivitis and periodontal disease, it stops the progression of lesions and reduces the recurrence of cavities without the need to make a cavity, it does not require anesthetics, it provides excellent aesthetic results in a single visit and it is possible to obtain good acceptance by patients.…”
Section: Treatmentmentioning
confidence: 99%

Dental fluorosis: a review

Rosas López Portillo,
Rosas Alcaraz,
Gámez Valenzuela
et al. 2024
Int J Res Med Sci
“…Las resinas infiltrativas ICON® tiene como principal compuesto matriz orgánica a base metacrilato, específicamente monómero trietilenglicol dimetacrilato (TEGDMA), iniciadores y aditivos (4,8). Es un material hidrófilo y sin relleno; además, la tensión superficial y el coeficiente de penetración son altas (5).…”
Section: Resinas Infiltrativasunclassified
“…Respecto al índice de Thylstrup y Fejerskov, brinda una escala del cero al nueve en la que evalúa las características clínicas en relación a los cambios histológicos que ocurren en los diferentes niveles de gravedad en la fluorosis, incluso de la acumulación de flúor en esmalte, mostrando criterios de validez biológica (15). Con mayor precisión, en la fluorosis leve se observan líneas opacas con zonas blanquecinas, en los casos de fluorosis moderada la mayoría de la superficie se encuentra opaca e incluso con cráteres y por último en la fluorosis severa la superficie del esmalte puede estar perdida en su totalidad dejándola susceptible a fractura, además la lesión puede adquirir un tono marrón (4,19).…”
Section: Gradosunclassified
See 1 more Smart Citation